Conceptual Principles of Research of the Problem of Formation of Professional and Pedagogical Worldview of the Future Teacher of Foreign Literature - Romanetz, Valentyna (Pedagogical Discourse, 2012)
The article presents the results of theoretical analysis of the problem of training of the future teacher of foreign literature, aimed at the formation of his professional and pedagogical worldview. Particular attention is paid to reflection of the conceptual foundations of organizing of this process.